Complications and the quality of life after surgical correction of medial patellar luxation in dogs - Rantén, Karin (2018)
Medial patellar luxation is one of the most common orthopedic disorders in dogs, especially in small breed dogs. It is, in most cases, a developmental disorder associated with skeletal deformities and malalignment of the extensor mechanism. Patellar luxation is classified into four grades, see Table 2. Surgical treatment is composed of bone reconstructive techniques and soft tissue reconstructive techniques and is often performed in dogs with patellar luxation grade 2-4. The most common complications after surgery are patellar reluxation and implant related complications, according to previous studies. In many studies, an increased risk of complications has been associated with the severity of the luxation. In most previous studies assessing the outcome of surgery, the objective has been the short-term outcome. Owner questionnaires that evaluate surgical outcome, compare treatment methods, assess chronic pain, function and quality of life has recently been used in several studies with dogs affected by orthopedic diseases.